Kombinasi Green Coagulant dan Adsorben GAC (Granular Activated Carbon) Sebagai Pengolahan Limbah Cair Batik - Farhan Athallah Ajiputra; Novirina Hendrasarie; Raden Kokoh Haryo Putro (Fakultas Teknik, 2022)
The batik industry, especially in the Jetis Sidoarjo batik home industry, in its production has several processes that produce waste in the form of waste, both in the form of solid, liquid and gas. This can cause pollution and have a direct impact on the surrounding environment, so the waste produced must first be treated before being discharged into the waters. This study aims to determine the level of effectiveness of each ingredient as a natural coagulant as well as the adsorption process in reducing levels of pollutant parameters, including Total Suspended Solid (TSS) and color in the liquid waste of the Jetis Sidoarjo batik industry. The method used is coagulation flocculation. The results of the best combination of green coagulant Moringa seeds pH 8 at a dose of 3500 mg/L, coconut coir pH 6 at a dose of 3500 mg/L, and dry gambas pH 6 at a dose of 3500 mg/L with GAC 50 gr and a sampling time of 60 minutes showed a decrease in the content of TSS parameters. and color respectively TSS 14 mg/L; color 84 Pt-Co, TSS 10 mg/L; color 54 Pt-Co TSS 26 mg/L; color 161 Pt-Co.